The Social Well-Being Issues of the European Urbanisation Stages and the Possibilities of their Management by the Creation of Spatial Configurations - Viktória Szirmai (DETUROPE)
Cities today play strategic roles in modernization processes as well as in the organization and operation of global economy. Big cities are the places where the conditions of modernisation, economic and social development, the operating conditions of global economy, the educated and qualified middle-class, members of the economic, political and cultural elite are concentrated. Meanwhile modern urban spaces are rather controversial. A variety of social problems, the traditional and new structures of local social inequalities, the historical and present day poverty, traditional and modern crime, environmental problems are all present. Various urban problems were also present in the historically changing stages of urban development. Taking the actual historical and social conditions into account, theories, criticisms, and various scientific approaches offered differentiated solutions - mainly based on spatial principals - to manage urban tensions. As urban conflicts keep reproducing and new tensions keep appearing these tools do not seem to succeed in managing these tensions, which is probably due to the one-dimensional aims of intervention. Management proposals regarding particular urbanisation stages were mainly based on spatial principals, they were one-dimensional, and they were not accompanied with schemes targeting structural effects. The aims of this study to present the various urban problems connected to the different urbanisation stages, as well as the proposals based on spatial principles which were aspiring to solve these problems and to evaluate these proposals. A further aim is to describe a complex structural management theory, which is very promising from the aspect of structural effects but lack the spatial approach. Finally this study aims to present a research whose aspiration is to connect the two different approaches empirically.